COV-19 BV model / Intan Nur Anatasha Kamal Ariffin, Nabihah Safiyah Mohd Azizan and Che Norhalila Che Mohamed - Kamal Ariffin, Intan Nur Anatasha; Mohd Azizan, Nabihah Safiyah; Che Mohamed, Che Norhalila (Universiti Teknologi MARA, Kedah, 2023)
The Malaysian public's acceptance of the COVID-19 vaccine booster is decreasing compared to the first and second doses. Some people believe that two doses of the vaccine are enough. This model was built to estimate the acceptance of taking the COVID-19 booster vaccine based on the health belief model (HBM) and demographic factors using the logistic regression model. There is no longer a model built to measure the acceptance of the COVID-19 vaccine booster, especially among Malaysians. From this model, each new user will know what the status of receiving the vaccine booster is (whether it is necessary to accept the booster vaccine or not) based on HBM and the demographic factors of the user. This model can be marketed to users aged 18 and above, especially Malaysians, regardless of race, age, or health status.